Analisis Kesuksesan Website Gratis Kabeh Dengan Pendekatan Delone And Mclean - Latifah Adi Triana; Septi Fajarwati; Ika Romadoni Yunita; Gustin Setyaningsih; Muhamad Awiet Wiedanto Prasetyo (Universitas Nurul Jadid, 2023)
The Kabeh Free Website is a system used for submitting population documents, the website is a solution for residents in Banyumas, especially those who are far from Purwokerto City, to be able to submit residence documents online without having to go to Dindukcapil. However, in practice, there are still residents who choose to register offline, while there are several complaints from the Banyumas community that there is no submission guide on the website, delays in confirmation via e-mail, users have difficulty submitting because the website is having an error. This is the reason for researchers to conduct research with the aim of knowing the success of the Gratis Kabeh website with the DeLone and McLean model and knowing which variables have an influence on the Gratis Kabeh website. The sample used in this study amounted to 250 samples with a purposive sampling technique. The method chosen is the DeLone and McLean Is Success Model, to determine the effect of the variables in this model. The results showed that the overall research hypothesis was accepted because it had a significant and positive effect, then the results of the F2 value showed a weak effect on the variables Information Quality, System Quality, Service Quality on Use and User Satisfaction, and the Usage variable on User Satisfaction and Net Benefit had a weak effect . However, the User Satisfaction variable has a moderate effect on Net Benefit